The Relationship between Physical Activity and the Incidence of Hypertension at the Work Area of the Ampenan Health Center - Dian Istiana; Dewi Nur Sukma Purqoti; Musmuliadin Musmuliadin; Baik Heni Rispawati; Fitri Romadhonika; Kaeleen Dingle (Universitas STRADA Indonesia, 2022)
The incidence of hypertension from year to year has a significant increase, many people with high blood presssure do not realize they have hypertension until they felt signs and symptoms. One of the supporting factors to keep tension stable is do physical activity regularly. The research purpose was to determine the relationship between physical activity and the incidence of hypertension. This research uses descriptive quantitative analysis method with cross sectional approach. The results of this study was the average respondent was 41 to 50 years old, the gender of more Female, all of respondence Had ever received information about hypertension, most of the respondents in the category of moderate physical activity and most of the respondents were in the normal blood pressure category, and and the results of bivariate analysis show p value = 0.142, it’s mean there is no relationship of physical activity with the incidence of hypertension.